Operation Mode of Integrated Energy System with Liquid Air Energy Storage. Issue 1 (1st January 2022) - Bai, Ning; Liu, Yixue; Jiang, Xiaoxia; Cui, Shuangshuang; Li, Haipeng; He, Qing
Abstract: This paper takes the energy supply in the park as the research background, the integrated energy system as the research object and establishes the integrated energy system model including liquid air energy storage, distributed photovoltaic, gas turbines and other equipment. When the integrated energy system operates the mode of "ordering heat by power", the heat wasted as high as 14.647MWh and the cold wasted as high as 24.13MWh. When the system is not equipped with LAES, the output power of the CCHP unit increases by 21MWh, the electricity purchase in power grid increases by 8.123MWh, the heat waste increases by 21.696MWh and the cold waste increases by 12.421MWh. When the integrated energy system operates the mode of [[CHECK_DOUBLEQUOT_ENT]] ordering power by heat ", heat energy of the system has been reasonably utilized. When the system is not equipped with LAES, the power output and heat of the CCHP unit in the system are the same, the thermal energy output results of the system are the same and the electricity purchased by the power grid increases by 32.14MWh.